Effect of Holstein and Beef-Dairy Cross Breed Description on the Sale Price of Feeder and Weaned Calf Lots Sold Through Video Auctions - E. D. McCabe; M. E. King; K. E. Fike; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Objectives were to determine: 1) value of Holstein feeder steer lots compared with steer lots of other breed descriptions, 2) value of beef-dairy cross weaned steer calves compared with either Holstein weaned calves or weaned calves of other breed descriptions, and 3) value of beef-dairy cross weaned calves compared with weaned calves of other beef breed descriptions sold through video auctions. Study Description:Data on 14,075 feeder steer lots sold in 211 auctions from 2010 through 2018; 763 weaned steer calf lots, and 1,125 weaned steer and heifer calf lots sold via seven auctions in 2020 and 2021 were used. Separate multiple regression models using backwards selection were developed for feeder cattle, weaned steer, and weaned steer and heifer calf lots. The five breed group categories used were English-English crossed, English-Continental crossed, Brahman-influenced, Holstein, and beef-dairy crossed (weaned calves). Results:Breed description of feeder steer, weaned steer calf, and weaned steer and heifer calf lots affected sale price (P<0.0001). Among weaned steer calves, beef-dairy crossed lots sold for the second lowest (P<0.05) price (147.62/cwt), though greater than Holsteins. Among feeder steer lots, Holsteins sold for the lowest (P<0.05) sale price (110.56/cwt) compared with all other breed groups. Among weaned steer and heifer calves, beef-dairy crosses sold for less than (P<0.05; 136.39/cwt) all other breed groups. The Bottom Line:Beef-dairy crosses have improved value prospect compared with Holstein steers in the beef supply chain.
Keywords: beef calves; beef on dairy; sale price